Estimation of genetic parameters for weaning weights and metabolic weights characteristics and post weaning in Brahman cattle - Manuel, M. [UNESP]; Cavani, L. [UNESP]; Menezes, T. J. [UNESP]; Millen, D. D. [UNESP]; Andrighetto, C. [UNESP]; Lupatini, G. C. [UNESP]; Fonseca, R. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The objective of this study was to estimate heritability and correlations of 36,505 animals, belonging to the Brazilian Association of Zebu Breeders. They were estimated by Restricted Maximum Likelihood method (REML) using Wombat software. The model included the direct additive genetic effect, maternal, permanent maternal environment and residual as random and fixed effects of contemporary group. The results of heritability ranged from 0,20 to 0,25 for weaning weight and yearling; 0,16 to 0,20 for real metabolic weaning, 0,21 to 0,25 for metabolic adjusted weight at weaning and yearling metabolic adjusted. The genetic correlations between weaning weight with metabolic real, weaning weight adjusted with metabolic are respectively 0,76 and 1,00. The genetic correlation between yearling weight and metabolic real, yearling weight adjusted metabolic were 0,97 and 1,00. Genetic correlations between weaning weight and yearling was 0,72, real metabolic weight at weaning and yearling real metabolic was 0,54, adjusted metabolic weight at weaning and yearling metabolic adjusted was 0,71. Genetic correlations between weight at weaning and adjusted metabolic and weight-adjusted metabolic year were 1,00 and 1,00. Therefore, the use of metabolic weight without age adjustment can warn the estimates.
Keywords: variance components; genetic correlation; heritability